2010
DOI: 10.1017/s0025315410001141
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of franciscana dolphins, Pontoporia blainvillei (Cetacea: Pontoporiidae) incidentally caught off southern Brazil and northern Argentina

Abstract: Age and length data of 291 franciscana dolphins (Pontoporia blainvillei) incidentally captured on the coast of Rio Grande do Sul State (RS), southern Brazil, were used to fit growth curves using Gompertz and Von Bertalanffy growth models. A small sample of franciscanas (N = 35) from Buenos Aires Province (BA), Argentina, were used to see if there are apparent growth differences between the populations. Male and female franciscana samples from both areas were primarily (78–85%) <4 years of age. The Von Berta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
1
33
1
2
Order By: Relevance
“…P. blainvillei is the only extant species of the family Pontoporiidae (May-Collado and Agnarsson, 2006;McGowen et al, 2009), and is one of the smallest cetaceans, maximum body length reported is 171 and 152 cm for females and males, respectively (Kasuya and Brownell, 1979;Botta et al, 2010). P. blainvillei, together with Inia geoffrensis, form the sister group to the Delphinoidea, which includes monodontids, porpoises, and ocean dolphins (Yan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…P. blainvillei is the only extant species of the family Pontoporiidae (May-Collado and Agnarsson, 2006;McGowen et al, 2009), and is one of the smallest cetaceans, maximum body length reported is 171 and 152 cm for females and males, respectively (Kasuya and Brownell, 1979;Botta et al, 2010). P. blainvillei, together with Inia geoffrensis, form the sister group to the Delphinoidea, which includes monodontids, porpoises, and ocean dolphins (Yan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Because the bay is formed by an estuary characterized by calm and shallow waters, an absence of large predators and is resource rich, it represents a high quality natural habitat were dolphins feed, rest, and reproduce, and where both dolphin populations show a high degree of residency (Cremer and Simões‐Lopes , Botta et al . , Hardt et al . ).…”
mentioning
confidence: 99%
“…), although further unpublished studies exist. This species is one of the smallest odontocetes; estimates of asymptotic length range from 129 to 158 cm for females and 113 to 136 cm for males, with long recognition that females are larger than males (Barreto & Rosas, 2006;Botta et al, 2010). Age at sexual maturation (ASM) reported in the above-mentioned studies range from 2.7 to 5 years for females at average lengths of 122-140 cm.…”
mentioning
confidence: 99%